When Do People Seek Internet Counseling? Exploring the Temporal Patterns of Initial Submissions to Online Counseling Services. Issue 2 (2nd April 2020) - Tirel, Maili; Rozgonjuk, Dmitri; Purre, Merle; Elhai, Jon D.
Abstract: Internet counseling can be a valuable resource for people who cannot seek mental health care due to various reasons. The aim of this study was to analyze the time patterns of first-time contacts made by clients to online counseling services. Data from two online counseling service providers, encompassing 3, 291 people, were analyzed. The results showed that people tended to contact online counselors during the seasons with less sunlight (winter and autumn), and during evening and afternoon. There were no pronounced day-of-week effects. These results support, to some extent, the seasonality and time-of-day patterns related to mental disorders and help-seeking.